Parents' Perception of Students on Virtual Account-Based Services - Jamaluddin, Jamaluddin; Dewi, Mustika; Darwis, Muh.; Awaluddin, M. (Universitas Negeri Makassar, 2022)
This study is a quantitative descriptive study that aims to determine how parents perceive students' virtual account-based services at the Al-Fityan School of Integrated Islamic Elementary School Gowa). The research method is descriptive quantitative with a population of 636 respondents with a sample of 95 respondents using a sampling technique using the probability sampling technique, namely simple random sampling. Data collection techniques used are observation, questionnaires, and documentation. The data analysis technique used is a descriptive analysis of percentages and distributions. The results showed that the perceptions of parents of students towards Virtual Account-based services belonged to the category of strongly agree in terms of the simplicity of Virtual Account-based services, clarity, and certainty of procedures/procedures for Virtual Account-based services, security of Virtual Account-based services, the openness of services. Virtual Account-based, efficient Virtual Account-based services, economical Virtual Account-based services, equitable justice in Virtual Account-based services, and timeliness in Virtual Account-based services. To achieve a good perception of Virtual Account-based services, efforts are made to increase customer satisfaction to achieve the goal of excellent service, namely to gain recognition for the quality of service that satisfies customers.